2016
DOI: 10.1080/2162402x.2016.1185583
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade reveals the stimulatory capacity of tumor-associated CD103+ dendritic cells in late-stage ovarian cancer

Abstract: Although immune infiltrates in ovarian cancer are associated with improved survival, the ovarian tumor environment has been characterized as immunosuppressive, due in part to functional shifts among dendritic cells with disease progression. We hypothesized that flux in dendritic cell subpopulations with cancer progression were responsible for observed differences in antitumor immune responses in early and late-stage disease. Here we identify three dendritic cell subsets with disparate functions in the ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Flies et al . observed that CD11c + CD11b − CD103 + cDC1s were absent in the peritoneal cavity of healthy mice but comprise up to 40% of DCs in ovarian tumor-bearing mice and retained T-cell stimulatory capacity in advanced disease 42 . Monocytes exposed to the appropriate conditions such as treatment with the immunostimulatory agents monosodium urate crystals and Mycobacterium smegmatis can become Mo-DCs and powerful activators of tumor-specific CD8 + T cells and anti-tumor immunity 43 , 44 .…”
Section: Heterogeneity Of Dendritic Cells In the Tumor Microenvironmementioning
confidence: 98%
See 1 more Smart Citation
“…Flies et al . observed that CD11c + CD11b − CD103 + cDC1s were absent in the peritoneal cavity of healthy mice but comprise up to 40% of DCs in ovarian tumor-bearing mice and retained T-cell stimulatory capacity in advanced disease 42 . Monocytes exposed to the appropriate conditions such as treatment with the immunostimulatory agents monosodium urate crystals and Mycobacterium smegmatis can become Mo-DCs and powerful activators of tumor-specific CD8 + T cells and anti-tumor immunity 43 , 44 .…”
Section: Heterogeneity Of Dendritic Cells In the Tumor Microenvironmementioning
confidence: 98%
“…Among CD11c + CD11b + cDC2s, Lair-1 expression further distinguishes stimulatory and immunoregulatory DC subsets, which are also enriched in TME. Interestingly, programmed death-ligand 1 (PD-L1) is expressed by Lair-1( hi ) immunoregulatory DCs and may contribute to local tumor antigen-specific T-cell dysfunction 42 . Like Mo-DCs, cDC2s were found to suppress cytotoxic T lymphocyte (CTL) function in tumor-bearing mice via L-arginine metabolism, among other potential modes of action 45 , which is consistent with a previous finding that increased breakdown of the amino acids arginine and tryptophan in tumor-associated DCs negatively impacts T-cell effector function 46 .…”
Section: Heterogeneity Of Dendritic Cells In the Tumor Microenvironmementioning
confidence: 99%
“…In addition, integrin engagement and focal adhesion kinase activation recruits Rac1 to regulate spreading and adhesion on the extracellular matrix [ 26 , 89 , 108 ]. Immune cells are an integral part of the ovarian cancer TME and perform immune suppressive and activating functions that are pivotal in disease pathology [ 109 , 110 ] and these cells serve as important therapeutic targets [ 111 , 112 ]. The best-studied example of immune cell coupling to Rac1 activation in ovarian cancer is through cytokine activation of CXCR4 as detailed in Section 4.2 and Section 6 .…”
Section: Pathways For Rac1 Activation By the Ovarian Tumor Microenmentioning
confidence: 99%
“…A recent study demonstrated a direct link between SPARC-governed collagenous matrix remodeling, LAIR-1 neutrophil engagement and the restraining of NET extrusion [173]. Notably, an immune-suppressive phenotype has also been attributed to LAIR-1 and PD-L1 highly expressed on tumor-associated dendritic cell population in late stage ovarian cancer [174]. Furthermore, cross-linking of LAIR-1 has been linked with suppression of cytotoxic T-cell activity [175].…”
Section: Tumor Ecm Regulates Tam and Tan Recruitment And Polarizationmentioning
confidence: 99%